The availability of six tracer medicines in private medicine outlets in Uganda - Birabwa, Catherine; Murison, Jude; Evans, Valerie; Obua, Celestino; Agaba, Amon; Waako, Paul; Pollock, Allyson (Journal of pharmaceutical policy and practice, 2014)
Many low income countries struggle to provide safe and effective medicines due to poor public health care infrastructure, budgetary constraints, and lack of human resource capacity. Private sector pharmacies and drug shops are used by a majority of the population as an alternative to public pharmacies. This study looks at the availability of six essential medicines in private drug outlets across Uganda. Methods: A standardised medicines availability survey developed by the World Health Organization and Health Action International was adapted for use in this project to collect availability data for six tracer medicines in 126 private medicine outlets across four districts in Uganda from September 2011 to October 2012. Results: Artemisinin-based combination treatments and metformin were the most commonly found medicines in the private medicine outlets surveyed. Ninty-nine percent of all outlets carried artemisinin-based combinations while 93% of pharmacies and 53% of drug shops stocked metformin. Oxytocin was found in one third of outlets surveyed. Fluoxetine was in 70% of pharmacies yet was not found in any drug shops. Rifampicin and lamivudine were found infrequently in outlets across all districts; 10% and 2%, respectively. Not all brands found in surveyed outlets were listed on the Ugandan National Drug Register. In particular, five unlisted brands of rifampicin were found in private medicine outlets. Conclusions: The regulatory process should be improved through the enforcement of outlet licensing and medicine registration. Additional studies to elucidate the reasons behind the use of private medicine outlets over the public sector would assist the government in implementing interventions to increase use of public sector medicine outlets.
Keywords: Essential medicines; Uganda; Medicine outlet; Pharmacy; Drug shop; Private sector